2017
DOI: 10.1039/c7ra07813g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies on the separation of cinnamyl acetate and cinnamaldehyde by adsorption onto a β-cyclodextrin polyurethane polymer

Abstract: In order to isolate cinnamyl acetate (CAc) and cinnamaldehyde (CA), which coexist in cinnamon oil, a crosslinked polymer of b-cyclodextrin polyurethane (CDPU) was synthesized via a facile route and investigated as a selective adsorbent. The successful crosslinking was confirmed by FTIR, TG-DSC, XRD, SEM and N 2 adsorption-desorption analysis. The adsorption mechanism was investigated through a series of instrumental analyses and theoretical calculations, indicating that the combination of noncovalent interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…3.1. Characterization of QAS-β-CDPU cm -1 and 1550cm -1 are attributed to stretching vibration of C=O and amide group [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1. Characterization of QAS-β-CDPU cm -1 and 1550cm -1 are attributed to stretching vibration of C=O and amide group [22].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 1155 cm -1 and 1440 cm -1 are severally corresponded to the stretching vibration of C-C/C-O and methylene. The peak at 1660 cm -1 and 1550cm -1 are attributed to stretching vibration of C=O and amide group [22].…”
Section: Desorption and Reusability Experimentsmentioning
confidence: 99%
“…It displayed a broad-spectrum antimicrobial effect against molds, yeast, and bacteria through its major active constituent, cinnamaldehyde [ 30 ]. Natural CEO is used in a wide variety of fields in spices, food medicine, cosmetic products, and agricultural chemicals due to the presence of chemical constituents, including cinnamaldehyde (70–88%), o -methoxycinnamaldehyde (4–12%), cinnamyl acetate (CAc, 0.5–10%), and benzaldehyde (0.5–1%) [ 31 , 32 ]. Two challenges stand against bringing CEO, or essential oils (EOs) in general, to biological applications or clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these merits, we have used the selective inclusion method for the isolation of several organic compounds with an aqueous solution of β‐CD . In a previous study, we reported that a β‐CD polyurethane polymer exhibited good adsorption selectivity for CAc over CA, thanks to the recognition ability of the β‐CD cavity …”
Section: Introductionmentioning
confidence: 99%
“…27,28 In a previous study, we reported that a b-CD polyurethane polymer exhibited good adsorption selectivity for CAc over CA, thanks to the recognition ability of the b-CD cavity. 29 In this study, b-CD was used for inclusion separation of CAc and CA. Firstly, the feasibility of the method was investigated in terms of the configuration and thermodynamic constants of inclusion complexes.…”
Section: Introductionmentioning
confidence: 99%